OC-045 High Definition White Light Endoscopy and I-Scan for small Colonic Polyp Evaluation : Results of the Hiscope Study. (4th June 2013) - Basford, P J; Longcroft-Wheaton, G R; Higgins, B; Bhandari, P
Abstract : Introduction: Standard definition white light endoscopy is inadequate for in-vivo characterisation of small colonic polyps. The ASGE has identified prediction of polyp surveillance intervals and negative predictive value for adenomatous histology of diminutive recto-sigmoid polyps as key targets for new technologies. High definition white light endoscopy is now available but there is little data on it's use. Methods: We aimed to examine the in-vivo characterisation accuracy of high definition white light endoscopy (HDWL) plus a novel electronic imaging modality – i-Scan (Pentax, Japan). Patients undergoing colonoscopy through the UK Bowel Cancer Screening Programme were prospectively recruited. All colonoscopies were performed by a single expert endoscopist with extensive experience in in-vivo diagnosis. Procedures were performed with Pentax EC-3890Li 1.2 Megapixel HD+ colonoscopes and EPKi processor. An initial classification & validation exercise was carried out to determine the optimum i-Scan settings for in-vivo diagnosis, and to develop a novel in-vivo diagnosis assessment tool. All polyps < 10mm in size were assessed sequentially with HDWL and i-Scan. Optical magnification was not used. Predicted histology (non-neoplastic, adenoma, cancer) was recorded for both modalities and compared to the final histopathological diagnosis as reported by an expert gastrointestinal pathologist. Predictions were rated as high or low confidence assessments. Results were analysed for sensitivity and specificity for neoplasia, overall accuracy, and negative predictive value for rectosigmoid polyps ≤5 mm as recommended by the ASGE PIVI statement. Results: 84 patients were recruited, in whom 209 polyps < 10 mm were included. Mean polyp diameter was 4.3mm, median 4mm. 134 polyps were neoplastic and 75 non-neoplastic. There were no significant differences in sensitivity (95.5% vs 97.0%) and specificity (89.3% vs 90.7%) for neoplasia and overall diagnostic accuracy (93.3% vs 94.7%) between HDWL and i-Scan. Negative predictive value for adenomatous histology of rectosigmoid polyps ≤5 mm was 100% with both modalities. Polyp surveillance intervals using in-vivo assessment of diminutive polyps were correct in 95% and 97% of patients with HDWL and i-Scan respectively. Conclusion: Excellent in vivo diagnostic accuracy, in excess of 90% can be achieved with HDWL alone. No significant gains in accuracy over HDWL were noted with i-Scan when used with a 1.2Megapixel HD colonoscope Both HDWL and i-Scan fulfil the ASGE criteria for 'resect and discard' and 'do not resect' strategies for diminutive polyps Disclosure of Interest: None Declared